The Influence of Good Corporate Governance and Intellectual Capital on Organizational Performance in Mining Sector Companies Listed on the IDX for the 2020-2024 Period - Rachel Ekawati; Lamhot Henry Pasaribu (Eduvest - Journal of Universal Studies, 2025)
In the era of intensifying global competition, companies in the Indonesian mining sector face mounting pressure to enhance organizational performance to maintain their market position and ensure long-term sustainability. The mining sector plays a crucial role in Indonesia's economy, contributing significantly to national GDP, yet it faces unique challenges including commodity price volatility, stringent regulatory requirements, and increasing demands for sustainable business practices. This study examines the influence of Good Corporate Governance and Intellectual Capital on Organizational Performance in Mining Sector Companies Listed on the IDX for the 2020-2024 Period. Survey data from 41 HR managers in IDX-listed mining companies were analyzed using multiple regression analysis. The results reveal that both GCG (β=0.291, p=0.001) and IC (β=0.264, p=0.001) have significant positive effects on organizational performance, explaining 55% of the variance in performance outcomes (R²=0.550). These findings confirm that applying good GCG principles and optimally managing IC contribute substantially to operational efficiency and competitive advantage. This research makes both practical and theoretical contributions by demonstrating the critical importance of implementing GCG and developing IC for companies seeking to improve performance and competitiveness amid industry challenges in the resource-intensive mining sector.